2023
DOI: 10.1038/s41467-023-38330-x
|View full text |Cite
|
Sign up to set email alerts
|

Unified theoretical framework for black carbon mixing state allows greater accuracy of climate effect estimation

Abstract: Black carbon (BC) plays an important role in the climate system because of its strong warming effect, yet the magnitude of this effect is highly uncertain owing to the complex mixing state of aerosols. Here we build a unified theoretical framework to describe BC’s mixing states, linking dynamic processes to BC coating thickness distribution, and show its self-similarity for sites in diverse environments. The size distribution of BC-containing particles is found to follow a universal law and is independent of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 51 publications
2
4
0
Order By: Relevance
“…Figure 2 shows the CT distributions (blue violin plots) in the three locations at different D BC values. The CTs at the three locations all show similar geometric means, which vary with different D BC values (yellow dots), specifically, 36.4 nm in Nanjing (Figure 2a), 11.0 nm in Tokyo (Figure 2b), and 22.0 nm in Sacramento (Figure 2c), as demonstrated in our previous study (J. Wang et al., 2023). Different shades of blue represent the number of particles, where a lighter blue indicates fewer particles.…”
Section: Methods and Datasupporting
confidence: 83%
See 3 more Smart Citations
“…Figure 2 shows the CT distributions (blue violin plots) in the three locations at different D BC values. The CTs at the three locations all show similar geometric means, which vary with different D BC values (yellow dots), specifically, 36.4 nm in Nanjing (Figure 2a), 11.0 nm in Tokyo (Figure 2b), and 22.0 nm in Sacramento (Figure 2c), as demonstrated in our previous study (J. Wang et al., 2023). Different shades of blue represent the number of particles, where a lighter blue indicates fewer particles.…”
Section: Methods and Datasupporting
confidence: 83%
“…The CTs at the three locations all show similar geometric means, which vary with different D BC values (yellow dots), specifically, 36.4 nm in Nanjing (Figure 2a), 11.0 nm in Tokyo (Figure 2b), and 22.0 nm in Sacramento (Figure 2c), as demonstrated in our previous study (J. Wang et al, 2023). (Bond et al, 2013) and mostly traffic sources (D. Liu et al, 2014).…”
Section: Observed Bc Microphysical and Mixing Propertiessupporting
confidence: 81%
See 2 more Smart Citations
“…As shown in the bottom panel of Figure 6, the ratio of E abs between model A and the core‐shell model is smaller than that of MAC, indicating that real aerosol absorption may be larger than inferred by the E abs observation. To match the low value of E abs from field observation, the BC absorption could be reduced by 40%–50% using a modified core‐shell model which directly adjusts the amount of coating material (J. Wang et al., 2023). In this study, it is found that the low E abs value of BC can be matched while the absorption is only reduced by approximately 11% using the encapsulated fractal aggregates model.…”
Section: Resultsmentioning
confidence: 99%